Fra syner og varsler til psykoterapi - Steffen, Vibeke (Tidsskrift for kulturforskning, 2016)
The capacity to receive occult messages and look into the future is claimed by individuals in most societies and probably always has been. A century ago, information of such indi-viduals was collected and saved in the Danish Folklore Archives as cultural heritage to be preserved for future generations. Time has shown, however, that the occult is still in demand. In present day Denmark as elsewhere, clairvoyance is a popular service offered at the alternative market for counselling and healing. In contrast to the seers of the past, whom we can only know from the accounts of folklorists and biographers, contemporary clairvoyants often present themselves in auto-biographies, in journals or television programmes and on the internet. Here, the concept of "the highly sensitive person" has emerged as a new term of reference to describe a specific personality trait characteristic of clairvoyants. This article demonstrates continuity in the perception of seers of the past and contemporary clairvoyants as particularly sensitive people although important changes have taken place regarding the ways in which their extraordinary capacities are practiced. This has had important consequences for their societal role and for the ways in which occult messages are communicated.